Using genomic data to revisit an early example of reproductive character displacement in Haitian Anolis lizards. Issue 15 (28th March 2013) - Lambert, Shea M.; Geneva, Anthony J.; Luke Mahler, D.; Glor, Richard E.
Abstract: The pattern of reproductive character displacement (RCD)—in which traits associated with reproductive isolation are more different where two species occur together than where they occur in isolation—is frequently attributed to reinforcement, a process during which natural selection acting against maladaptive mating events leads to enhanced prezygotic isolation between species or incipient species. One of the first studies of RCD to include molecular genetic data was described 40 years ago in a complex of Haitian trunk anole lizards using a small number of allozyme loci. In this example, Anolis caudalis appears to experience divergence in the color and pattern of an extensible throat fan, or dewlap, in areas of contact with closely related species at the northern and southern limits of its range. However, this case study has been largely overlooked for decades; meanwhile, explanations for geographic variation in dewlap color and pattern have focused primarily on adaptation to local signalling environments. We reinvestigate this example using amplified fragment length polymorphism (AFLP) genome scans, mtDNA sequence data, information on dewlap phenotypes and GIS data on environmental variation to test the hypothesis of RCD generated by reinforcement in Haitian trunk anoles. Together, our phenotypic and genetic results are consistent with RCD at the southern and northern limits of the range of A. caudalis . We evaluate the evidence for reinforcement as the explanation for RCD in Haitian trunk anoles, consider alternative explanations and provide suggestions for future work on the relationship between dewlap variation and speciation in Haitian trunk anoles. Abstract : See also the Perspective by Losos and Leal